Hydrothermal synthesis of boehmite in cellular alumina monoliths for catalytic and separation applications. Issue 11 (October 2015) - Vitorino, Nuno M.D.; Kovalevsky, Andrei V.; Abrantes, João C.C.; Frade, J.R.
Abstract For the first time, controlled hydrothermal functionalization was performed in porous cellular α-Al2O3 ceramics, targeting potential separation and catalytic processes for sustainable chemistry applications. Growth of micro-nano hierarchical structures of boehmite (γ-AlOOH) with high aspect ratio was assessed by SEM/EDS/XRD/FTIR. The pH and precursors concentration determine the growth mechanism and final functionalization level. The obtained results anticipate strategies for promoting formation of boehmite at the pores surfaces and tuning its morphology, including pre-treatments of the cellular matrix to increase the concentration of the surface defects and preliminary saturation of the pores with appropriate precursors to achieve uniform functionalization. Thus grown boehmite structures can be easily converted to γ-Al2O3 by thermal treatment while retaining the former distribution and aspect ratio, opening new possibilities for preparation of γ-Al2O3 supported catalysts.